1999
DOI: 10.1002/(sici)1521-3862(199908)5:4<165::aid-cvde165>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD of Aluminum Oxide/Hydroxide onto Organic Self-Assembled Monolayers

Abstract: We demonstrate the deposition of Al x O y H z onto hydroxy-terminated self-assembled monolayers. The layer structure is investigated by Fourier transform infrared (FTIR) spectroscopy, spontaneous desorption time-of-flight mass spectrometry, and surface plasmon spectroscopy. It is found that the organic self-assembled monolayer remains intact during deposition and the film thickness of the aluminum oxide and hydroxide films can be adjusted by varying the deposition time. The new aluminum hydroxide surface was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…There has still been limited reporting of the application of SSIMS to relatively ionic materials (see Refs 7, 24, 27–29 and the review by Adriens et al 3). One directly comparable system is the MOCVD‐deposited aluminium oxide/hydroxide films reported by Wohlfart et al 30 Spontaneous desorption ToF mass spectrometry was used to examine the composition of Al, O and OH thin films deposited on a gold thiol self‐assembled monolayer. Although indexed in a slightly different manner, the molecular ions observed are essentially identical to those reported here.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…There has still been limited reporting of the application of SSIMS to relatively ionic materials (see Refs 7, 24, 27–29 and the review by Adriens et al 3). One directly comparable system is the MOCVD‐deposited aluminium oxide/hydroxide films reported by Wohlfart et al 30 Spontaneous desorption ToF mass spectrometry was used to examine the composition of Al, O and OH thin films deposited on a gold thiol self‐assembled monolayer. Although indexed in a slightly different manner, the molecular ions observed are essentially identical to those reported here.…”
Section: Resultsmentioning
confidence: 89%
“…As demonstrated in the indexing of Wohlfart et al ,30 the ions observed are unambiguous in terms of their mass assignment, but ambiguous in how the stoichiometry of the ion is reported. For example, the mass difference between each member of a family Al x O y is 18 Da.…”
Section: Resultsmentioning
confidence: 99%
“…49 On an uSH terminated SAM, sufficiently short exposures to cyclopentadienyl-allyl-palladium, ͑C 5 H 5 ͒Pd͑C 3 H 5 ͒ lead to a plateau in Pd coverage. Such properties may be useful for devices that require a robust electrical connection between the ͑metal͒ electrodes and the organic without causing disruptions to the organic molecule or short circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Although the formation of organic films on inorganic surfaces (organic/inorganic) has been studied extensively, in particular, in the development of organic field effect transistors [1], detailed studies on the deposition of inorganic films onto organic surfaces (inorganic/organic) have been dominated by metals deposited on self-assembled monolayers (SAMs) [2][3][4][5]. However, various metal oxides are also of interest in developing the encapsulation films on organic surfaces [6][7][8][9]. In this paper, we describe the growth of aluminum oxide (AlO x ) on CH 3 -terminated SAMs (hydrophobic surfaces) by atomic layer deposition (ALD) (Model Savanna 100, Cambridge NanoTech, Inc., Cambridge, Massachusetts, USA) at low temperature to minimize the chemical and physical impact on the organic layers.…”
mentioning
confidence: 99%